Characterization of free, conjugated, and bound phenolics in early and late ripening kiwifruit cultivars. (25th February 2021) - Gao, Yuan; Ping, Hua; Li, Bingru; Li, Yang; Zhao, Fang; Ma, Zhihong
Abstract: BACKGROUND: Kiwifruit ( Actinidia ) has long been called the 'king of fruits' because of its unique flavor and the wide range of bioactive compounds which contains ascorbic acid, phenolics and minerals. These bioactivities are influenced by species and cultivar. However, to date few studies are concerned with the effect of ripening time on fruit quality. Here, early and late ripening kiwifruits were investigated to determine their content of ascorbic acid, organic acid, and phenolic compounds. RESULTS: Early ripening cultivars contained higher quinic acid and malic acid, while citric acid were found in large amounts in late ripening kiwifruits. Most of the early ripening cultivars contained higher free phenolic fractions than the late ripening fruits, mainly due to the high levels of epicatechin. However, conjugated phenolics, mainly including caffeic and 2, 3, 4‐trihydroxybenzoic acid, achieved higher levels in the late ripening cultivars. Free phenolics were higher than conjugated phenolics in the early ripening cultivars. Principal component analysis revealed some key compounds that differentiated the kiwifruits, and all the kiwifruits were divided into two subgroups as early and late ripening cultivars. CONCLUSION: Ripening time had a great impact on the accumulation of bioactive compounds. The early ripening cultivars, compared to the late ripening ones, were characterized by higher levels of free neochlorogenic acid and epicatechin, while the late ripening kiwifruits contained higher amounts of conjugated phenolics. Results from this study provide further insights into the health‐promoting phenolic compounds in kiwifruit, and also provide good evidence to aid consumer selection. © 2021 Society of Chemical Industry